2005
DOI: 10.1128/jb.187.1.266-275.2005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diversity of a Putative Virulence Factor: Purification and Characterization of Isoforms of an Extracellular Serine Glutamyl Endopeptidase of Enterococcus faecalis with Different Enzymatic Activities

Abstract: A previously identified gene sprE of Enterococcus faecalis strain OG1 was shown to encode an extracellular serine protease that appears to belong to the glutamyl endopeptidase I staphylococcal group. A single form of SprE with a molecular mass of 25 kDa and a pH optimum between 7.0 and 7.5 was isolated from culture supernatant of wild-type E. faecalis strain OG1RF (TX4002); this form was apparently generated by cleavage of the Ser ؊1 -Leu 1 and Arg 230 -Leu 231 peptide bonds of the secreted zymogen. In contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 65 publications
3
46
1
Order By: Relevance
“…Subsequent analysis of gelatinase activity, as measured by proteolysis of Azocoll, indicated a clear correlation between gelatinase activity of bacteria grown in tissue culture medium plus T84 cells and translocation: the gelE disruption mutant showed no detectable activity against Azocoll, the gelE deletion mutant showed a minimal amount of activity (OD 540 of 0.1 Ϯ 0.1 compared to 2.3 Ϯ 0.3 for OG1RF), and complementation fully restored activity (OD 540 of 2.7 Ϯ 0.1). The residual proteolytic activity shown by the gelE deletion mutant is likely due to production of a superactive serine protease in this mutant (6), the activity of which is different from that of SprE in wild-type OG1RF due to different processing (6).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent analysis of gelatinase activity, as measured by proteolysis of Azocoll, indicated a clear correlation between gelatinase activity of bacteria grown in tissue culture medium plus T84 cells and translocation: the gelE disruption mutant showed no detectable activity against Azocoll, the gelE deletion mutant showed a minimal amount of activity (OD 540 of 0.1 Ϯ 0.1 compared to 2.3 Ϯ 0.3 for OG1RF), and complementation fully restored activity (OD 540 of 2.7 Ϯ 0.1). The residual proteolytic activity shown by the gelE deletion mutant is likely due to production of a superactive serine protease in this mutant (6), the activity of which is different from that of SprE in wild-type OG1RF due to different processing (6).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria used (Table 1) include wild-type OG1RF (Gel ϩ , Spr ϩ ) (13), the fsrB deletion mutant TX5266, and the gelE insertion disruption mutant TX5128 (10,21); the latter two are Gel Ϫ using a standard plate assay, (20,21) and by Northern blot analysis we had previously shown that gelE and sprE are cotranscribed in OG1RF and no sprE mRNA is detected in TX5128 (21). TX5283 (20) is the fsrB deletion mutant TX5266 containing the shuttle vector pTCV-lac with promoterless lacZ (19), while TX5286 is TX5266 carrying pTEX5270 (gelE promoter::lacZ fusion in pTCV-lac) (20).…”
Section: Methodsmentioning
confidence: 99%
“…Seminal work has demonstrated the ability of GelE secreted from E. faecalis to degrade casein (40). E. faecalis V583 cells and CCM exhibited the ability to degrade casein ( Fig.…”
Section: E Faecalis V583 Ccm Exhibits Caseinolytic Activity That Is mentioning
confidence: 99%